Efficacy, safety and usability of secukinumab administration by autoinjector/pen in psoriasis: a randomized, controlled trial (JUNCTURE). (22nd September 2014) - Paul, C.; Lacour, J.‐P.; Tedremets, L.; Kreutzer, K.; Jazayeri, S.; Adams, S.; Guindon, C.; You, R.; Papavassilis, C.; the JUNCTURE study group
Abstract Background Secukinumab is a fully human anti–interleukin‐17A monoclonal antibody. Objective Determine the efficacy, safety and usability of secukinumab administered via autoinjector/pen. Methods This phase III trial randomized subjects with moderate to severe plaque psoriasis to secukinumab 300 mg, 150 mg or placebo self‐injection once weekly to Week 4, then every 4 weeks. Co‐primary end points at Week 12 were ≥75% improvement in Psoriasis Area and Severity Index (PASI 75) and clear/almost clear skin by investigator's global assessment 2011 modified version (IGA mod 2011 0/1). Secondary end points included autoinjector usability, assessed by successful, hazard‐free self‐injection and subject‐reported acceptability on Self‐Injection Assessment Questionnaire. Results Week 12 PASI 75 and IGA mod 2011 0/1 responses were superior with secukinumab 300 mg (86.7% and 73.3%, respectively) and 150 mg (71.7% and 53.3%, respectively) vs. placebo (3.3% and 0%, respectively) (P < 0.0001 for all). All subjects successfully self‐administered treatment at Week 1, without critical use‐related hazards. Subject acceptability of autoinjector was high throughout 12 weeks. Adverse events were higher with secukinumab (300 mg, 70.0%; 150 mg, 63.9%) vs. placebo (54.1%), with differences largely driven by mild/moderate nasopharyngitis. Conclusion Secukinumab delivered by autoinjector/pen is efficacious, well‐tolerated and associated with high usability in moderate to severe plaque psoriasis.